GERIBEL Book Assisted by the Book Creator Application for Elementary School Dance Arts Learning - Felin Dyah Nur Arifah; Deasylina da Ary (LPPM Undiksha, 2025)
Dance education teacher learning still does not use learning media optimally, learning is less varied and monotonous, and teachers do not master the learning materials. This study aims to create a GERIBEL book learning media assisted by the Book Creator application in dance education subjects. This Research and Development (R&D) study uses the ADDIE development model. Data collection techniques use interviews, observations, questionnaires, tests, and documentation. Data analysis techniques use quantitative descriptive techniques. The study subjects were material expert validators, media expert validators, grade IV teachers and grade IV elementary school students. Material experts have validated the media by obtaining a score of 90% of the